Control After the Release of Goods: Objectives, Forms, Methods of Customs Inspection; Proceedings of Fourteenth TheIIER International Conference, Paris, France, 8th March 2015 - Kolomytseva V. V. Valeriya Valerjevna; Bleikher O. V. Oksana Vladimirovna; Soskovets (Soskovec) L. I. Lubov Ivanovna; Ragozin D. V. Dmitrii Valerievich; Lysunets (Lysuneth) T. B. Tatiana Borisovna (2015, 2015)
Title screen